Wild vertebrates roadkill aggregations on the BR-050 highway, state of Minas Gerais, Brazil - Carine Firmino Carvalho; Ana Elizabeth Iannini Custódio; Oswaldo Marçal Junior (Bioscience Journal, 2015)
Researches on roadkill aggregations are important tools for wildlife conservation. The objective of this study was to determine wild vertebrate roadkill aggregations on a stretch of 96 kilometersof the BR-050 highway, between the cities of Uberlândia and Uberaba, State of Minas Gerais, Brazil. The survey was conducted between April 2012 and March 2013. Roadkill monitoring was performed by car, at a speed of approximately 60 km/h, and forty two (42) weekly trips, totaling 8064 km, were performed. The 2D Ripley's K-Statistics test from the Siriema v1.1 program was used to detect the scales of roadkill aggregations and 2D HotSpot Identification test was used to identify the location of these hotspots. Aggregations extended from the following kms: 14 to 33, 38, 41 to 51, 66 to 70 and 78 to 94. We found roadkill aggregations for wild vertebrates and mammals. The roadkill aggregations were significant for Euphractus sexcinctus, Conepatus semistriatus, Procyon cancrivorus, Hydrochoerus hydrochoerus, Cariama cristata, Boa constrictor amarali and Crotalus durissus collilineatus according to the taxonomic specific level. Thus, it is suggested that mitigation measures for vertebrate conservation must be implemented in the indicated areas.